Pengaruh Program Magang Mandiri terhadap Kesiapan Kerja Mahasiswa Fakultas Ekonomika dan Bisnis Angkatan 2022 Universitas Boyolali (UBY) - Dika Rahayuningsih; Lusiana Herawati; Anisa Putri Anggraini; Unna Ria Safitri (MASMAN Master Manajemen, 2026)
This study examines the effect of the Independent Internship Program on the work readiness of students from the Faculty of Economics and Business, University of Boyolali, class of 2022. The high unemployment rate among university graduates indicates a mismatch between academic competencies and labor market demands. This research employed a qualitative descriptive approach. Data were collected through in-depth interviews, observations, and documentation involving students who participated in the internship program. The results indicate that the Independent Internship Program plays an important role in improving students’ work readiness, particularly in terms of work skills, professional attitudes, and self-confidence. However, the effectiveness of the program is highly influenced by the quality of supervision, relevance of internship placement, and active student participation. These findings imply that universities need to strengthen the quality-oriented management of internship programs to better prepare graduates for the labor market.